2002
DOI: 10.1046/j.1365-8711.2002.05144.x
|View full text |Cite
|
Sign up to set email alerts
|

The location of cosmic microwave background peaks in a universe with dark energy

Abstract: A B S T R A C TThe locations of the peaks of the cosmic microwave background (CMB) spectrum are sensitive indicators of cosmological parameters, yet there is no known analytic formula which accurately describes their dependence on them. We parametrize the location of the peaks as l m ¼ l A ðm 2 w m Þ, where l A is the analytically calculable acoustic scale and m labels the peak number. Fitting formulae for the phase shifts w m for the first three peaks and the first trough are given. It is shown that in a wide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
113
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(118 citation statements)
references
References 15 publications
(32 reference statements)
5
113
0
Order By: Relevance
“…Practically the same information is contained in a few characteristics such as the amplitude and inclination of the power spectrum at COBE scale and the amplitudes and locations of the observed acoustic peaks and dips. Indeed, it was shown (see Hu & Sugiyama 1995;Hu & White 1996;Efstathiou & Bond 1999;Doran & Lilley 2002 and references therein) that the sensitivity of the locations and amplitudes of the extrema, especially of the peaks, to cosmological parameters is the same as their sensitivity to the flat band powers, the C l values, from presently available data. This is not surprising: the extrema have an obvious physical interpretation and have the largest weight among data points on the CMB power spectrum as a result of a minimal ratio of error to value.…”
Section: Introductionmentioning
confidence: 98%
“…Practically the same information is contained in a few characteristics such as the amplitude and inclination of the power spectrum at COBE scale and the amplitudes and locations of the observed acoustic peaks and dips. Indeed, it was shown (see Hu & Sugiyama 1995;Hu & White 1996;Efstathiou & Bond 1999;Doran & Lilley 2002 and references therein) that the sensitivity of the locations and amplitudes of the extrema, especially of the peaks, to cosmological parameters is the same as their sensitivity to the flat band powers, the C l values, from presently available data. This is not surprising: the extrema have an obvious physical interpretation and have the largest weight among data points on the CMB power spectrum as a result of a minimal ratio of error to value.…”
Section: Introductionmentioning
confidence: 98%
“…One of the features of this model is the variation of equation of state during the expansion of the universe. Various Quintessence models like k-essence [10], tachyonic matter [11], Phantom [12,13] and Chaplygin gas [14] provide various equations of states for the dark energy [13,14,15,16,17,18,19,20,21].…”
mentioning
confidence: 99%
“…Driving effects from the decay of the gravitational potential as well as contributions from the Doppler shift of the oscillating fluid introduce a shift in the spectrum. A good parameterization for the location of the peaks and troughs is given by [40,41] …”
Section: B Cmbr Shift Parametermentioning
confidence: 99%
“…The location of first acoustic peak can be determined in model by equation (39) with φ 1 (ω m , ω b ) ≃ 0.27 [40,41]. It is easily shown that shift parameter is as follows [42]:…”
Section: B Cmbr Shift Parametermentioning
confidence: 99%
See 1 more Smart Citation